Asal Terkenal, Bisa Terpilih: Peran Political Parasocial Relationship terhadap Voting Tendencies Pada Pemilih Pemula - Lintang Kheisa Permana; Ilham Nur Alfian (Universitas Airlangga, 2023)
Political figures or candidates can create personas in the media to attract voters and maintain loyalty based on parasocial relationships. Parasocial relationships are essentially a concept that has existed for a long time and is now expanding and extending into the realm of politics. Currently, studies are emerging on the connection between parasocial relationships and voting tendencies among political figures or candidates, particularly among first-time voters, as well as the factors that strengthen or weaken parasocial relationships. Through a systematic review, the research findings indicate a strong correlation between parasocial relationships and voting tendencies, especially among first-time voters. Furthermore, the factors influencing the strength of parasocial relationships to enhance electability include media exposure, celebrity endorsements, narrative transportation, and the candidate's persona in the media. However, one limitation of this study is that the journal sources predominantly come from the United States compared to other countries. Therefore, this topic remains highly interesting for further research.